2010
DOI: 10.1111/j.1476-5381.2010.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

6‐Shogaol, an active constituent of ginger, inhibits breast cancer cell invasion by reducing matrix metalloproteinase‐9 expression via blockade of nuclear factor‐κB activation

Abstract: BACKGROUND AND PURPOSEShogaols are reported to possess anti-inflammatory and anticancer activities. However, the antimetastatic potential of shogaols remains unexplored. This study was performed to assess the effects of shogaols against breast cancer cell invasion and to investigate the underlying mechanisms. EXPERIMENTAL APPROACHThe anti-invasive effect of a series of shogaols was initially evaluated on MDA-MB-231 breast cancer cells using the matrigel invasion assay. The suppressive effects of 6-shogaol on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 43 publications
7
119
0
Order By: Relevance
“…The present study also indicated that hispolon suppressed the secretion and expression of MMP-9 in a dose-dependent manner in TPA-induced MDA-MB-231 cells. The mature form of MMP-9 (92 kDa, upper band) possessed gelatinolytic activity and was detected outside the cells, while the precursor form (85 kDa, lower band) remained inside the cells; these findings were consistent with the results of previous studies (24,25). Transcriptional regulation of MMP-9 has been proposed to be vital in its activation (26).…”
Section: Discussionsupporting
confidence: 91%
“…The present study also indicated that hispolon suppressed the secretion and expression of MMP-9 in a dose-dependent manner in TPA-induced MDA-MB-231 cells. The mature form of MMP-9 (92 kDa, upper band) possessed gelatinolytic activity and was detected outside the cells, while the precursor form (85 kDa, lower band) remained inside the cells; these findings were consistent with the results of previous studies (24,25). Transcriptional regulation of MMP-9 has been proposed to be vital in its activation (26).…”
Section: Discussionsupporting
confidence: 91%
“…Also, Habib et al (2008) reported that ginger might act as an anti-inflammatory and anti-cancer (Habib et al, 2008). The dried rhizomes of ginger (rich in pungent phenolic compounds: gingerols and shogaols) or extracts thereof are important ingredients of many traditional/ alternative medicines worldwide (Ling et al, 2010). Both of 6-shogaol and 6-gingerol can significantly inhibit the down-regulation of adiponectin expression (Yasuka et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Asian countries, ginger has also been used as an herbal medicine to treat a wide range of disorders such as inflammation, dyspepsia, nausea, vomiting, pain, the common cold and diarrhoea (Ling et al, 2010). Ginger extract has antioxidant properties and scavenges superoxide anion and hydroxyl radicals (Afshari et al, 2007).…”
Section: Change In Adiponectin and Oxidative Stress After Modifiable mentioning
confidence: 99%
“…[6]-Shogaol, one of the active ingredients in ginger, was identified to possess a surprisingly wide range of beneficial properties. It has been reported that [6]-shogaol can inhibit breast cancer cell invasion by reducing matrix metalloproteinase-9 expression via the blockade of nuclear factor-kappaB activation [24] .…”
Section: Discussionmentioning
confidence: 99%
“…[6]-Shogaol, an active ingredient in ginger, was previously reported to possess anti-cancer and anti-inflammatory properties [23,24] . However, despite many published reports, the effect of [6]-shogaol on melanogenesis is unknown.…”
Section: Introductionmentioning
confidence: 99%